Upaya Optimalisasi Kesiapan Alat – Alat Pemadam Kebakaran Dalam Menjaga Keselamatan di Atas Kapal - Wilastari, Santhi; Wibowo, Syailendra (Universitas Ivet, 2021)
The objectives discussed in this paper are to answer the questions in the subject matter, namely to increase understanding of safety equipment, especially fire fighting equipment. So that it can optimize its performance. Increase the level of readiness of fire extinguishers so that whenever and whenever fire extinguishers have to be used they will be maximally used. OHS officers are people who work with the task of occupational health and safety as well as operating and maintaining fire extinguishers so that fires can be prevented. Where the duties and responsibilities must be carried out and accounted for properly according to orders from the leadership of the company. Fire extinguishers are one of the countermeasures and minimize the occurrence of fire hazards. So the role of fire extinguishers is very important, fire fighting is an action that must be taken to create a safe and efficient work environment. Skills include knowledge of fire extinguishers and the responsibilities that must be carried out. Therefore, it is very necessary to improve the skills of OHS officers, namely by increasing the material for the discussion of fire extinguishers, carrying out fire extinguishing exercises and maintaining and checking fire extinguishers.